STATISTICAL FACTOR ANALYSIS OF THE SLAGS CHARACTERISTICS OF STEEL-MAKING - V. F. Sobolev; N. V. Andrianov; A. A. Chichko (Литьë и металлургия)
The regression equations, reflecting interaction of the slag characteristics and its chemical composition, are received on the basis of multivariate regressive analysis using empirical evidence. Statistical estimate of degree of influence of the slag composition factors on foaming index and parameter considering surface tension, density and viscosity of slag is presented.